Synthesis and characterization of a solid solution series of the type Bi2MxMn4-xO10 (M = Cr3+, Co3+ and 0.0 ≤ x ≤ 2.0.) (Journal of Bangladesh Academy of Sciences, 2021)
Bi2Mn4O10 was synthesized from corresponding metal salts in glycerin by using an organic precursor-based glycerin nitrate method. The precursor was heated at various temperatures (300 – 800 °C) for about 18 hours to determine the lowest synthesis temperature for the formation of Bi2Mn4O10. The XRD patterns of the calcined samples revealed that the desired mullite type phase started to form at 600 °C, which became more crystalline with further increase of calcination temperature. Attempts were also taken to prepare chromium and cobalt incorporated solid solution series with nominal composition Bi2MxMn4-xO10 (M = Cr3+ and Co3+) by the same procedure. The XRD data of these series exhibited mullite type single phase up to x = 0.7 and 0.1 compositions for chromium and cobalt, respectively. For further insertion of M, an extra phase appeared along with the mullite type phase.J. Bangladesh Acad. Sci. 45(1); 13-26: June 2021